Comparison of the fineness and mechanical properties of hemp fiber conditionned in two different relative humidity environments - Decker, Aurélie; Tritter, Adrien; Sarazin, Vivien; Harzallah, Omar; Drean, Jean-Yves (Wydawnictwo Politechniki Łódzkiej, 2022)
Bast fiber, like hemp, has an affinity for water [1,2]. The moisture content of hemp fiber increased with the increasing of relative humidity [1]. The relative humidity changes the fiber properties [2,3] studied by LPMT (Laboratoire de Physique et de Mécanique Textile) in Mulhouse, France. A comparison of the fiber properties measured in two different relative humidity environments (30% and 60%) was studied. The fiber was placed between two specific cardstock frameworks with glue. The fineness was determined from the diameter measured with a projection microscope. Then, the tensile test was realised with MTS® , tensile testing instrument, to determine the breaking force, strain and stress and the Young’s modulus. The hemp fiber was manually extracted from unretted stem. The cultivar used was Santhica 27 cultivated in the East of France [4] by SADEF, a plant nutrition expert. The impact of the relative humidity environment on the fiber properties was not constant. The tensile tests realised in this study were not homogeneous. Dispersion of the results could be caused by bast fiber multi-scale. The selection caused more variability of fiber properties than the relative humidity for hemp fiber.
Keywords: hemp; fiber; mechanical properties; relative humidity; fineness; konopie; włókno; właściwości mechaniczne; wilgotność względna; rozdrobnienie